2021
DOI: 10.1016/j.jtbi.2021.110761
|View full text |Cite
|
Sign up to set email alerts
|

Application of a novel mathematical model to identify intermediate hosts of SARS-CoV-2

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Identifying intermediate hosts is also significant for mitigating the negative effects of infectious diseases. During the COVID-19 pandemic, scholars have also proposed a mathematical model to identify possible intermediate host species of emerging zoonoses based on ecological data of species and epidemiological data of pathogens [138] . Mathematical models could also inform the development, licensing, and decision-making of SARS-CoV-2 vaccines [139] .…”
Section: Global Multi-scale Epidemic Prediction Model and Systemmentioning
confidence: 99%
“…Identifying intermediate hosts is also significant for mitigating the negative effects of infectious diseases. During the COVID-19 pandemic, scholars have also proposed a mathematical model to identify possible intermediate host species of emerging zoonoses based on ecological data of species and epidemiological data of pathogens [138] . Mathematical models could also inform the development, licensing, and decision-making of SARS-CoV-2 vaccines [139] .…”
Section: Global Multi-scale Epidemic Prediction Model and Systemmentioning
confidence: 99%
“…Royce et al . proposed that mink, pangolin, and ferret are the intermediate hosts of SARS-CoV-2 through a new mathematical model method ( Royce, 2021 ). However, molecular biology and phylogenetic analysis showed that pangolin coronavirus (pangolin-CoV-2020) was genetically related to SARS-CoV-2, but SARS-CoV-2 was not directly derived from pangolin-CoV-2020 ( P Liu et al., 2020 ; Xiao et al., 2021 ).…”
Section: Cross-species Transmission Of Sars-cov-2mentioning
confidence: 99%
“…It emerged in Wuhan China and spread throughout China and globally through human mobility. Bats are believed to be the natural host of SARS-CoV-2 while zoonotic transfer and spillover through mammals such as ferrets, pangolins and mink are thought to be potential intermediate hosts to infect humans [1][2][3][4]. The World Health Organization (WHO) declared COVID-19 a Public Health Emergency of International Concern (PHEIC) [1] on 30 January 2020.…”
Section: Introductionmentioning
confidence: 99%